2014
DOI: 10.1182/blood.v124.21.1305.1305
|View full text |Cite
|
Sign up to set email alerts
|

Development of Quality Metrics to Evaluate Pediatric Hematologic Oncology Care in the Outpatient Setting

Abstract: Introduction: Systems to quantify and incentivize quality of care (QoC) have been developed in multiple healthcare settings. In pediatric oncology, lists of QoC metrics or recommendations have been procured through consensus methodologies such as the Delphi process. To date, no QoC metrics have been developed for outpatient pediatric oncology. Objectives: The aim of this study was to develop a list of QoC metrics for the leukeumia-lymphoma (LL) clinic at the Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This study continues along the same lines of previous studies into QI feasibility, in other areas of healthcare, where QIs are increasingly being used, such as adult cancer, 25–27 cardiovascular disease, 28 and rheumatology 29 . Knops et al 17 underlined the importance of development of QIs for childhood cancer, and in the past two decades, some sets of QIs have been proposed for pediatric oncology care 30–35 . However, no prior studies were found that investigated NBL QIs specifically.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This study continues along the same lines of previous studies into QI feasibility, in other areas of healthcare, where QIs are increasingly being used, such as adult cancer, 25–27 cardiovascular disease, 28 and rheumatology 29 . Knops et al 17 underlined the importance of development of QIs for childhood cancer, and in the past two decades, some sets of QIs have been proposed for pediatric oncology care 30–35 . However, no prior studies were found that investigated NBL QIs specifically.…”
Section: Discussionmentioning
confidence: 65%
“…29 Knops et al 17 underlined the importance of development of QIs for childhood cancer, and in the past two decades, some sets of QIs have been proposed for pediatric oncology care. [30][31][32][33][34][35] However, no prior studies were found that investigated NBL QIs specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy‐related quality indicators have been developed in international adult and pediatric oncology studies that may be relevant to nursing. Such indicators reflect structures, processes, and outcomes such as: chemotherapy administration competency, closed system transfer devices; administration delays, documented start and stop times/scheduled delivery, guideline‐adherent processes, personal protective equipment use; and drug dose errors (Bradley et al, 2013a; Looper et al, 2016; Teichman et al, 2017). Potential indicators nominated by expert panelists in Round One open‐ended responses include: patient identification; safe medication administration; adverse event documentation; and extravasation rates (Jackson‐Rose et al, 2017; Looper et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Pain assessment and management is a well‐established NSI in adults and pediatrics (Montalvo, 2007; Start et al, 2018). It has also been selected as a pediatric oncology quality indicator for HIC and LMIC (Teichman et al, 2017; Wong et al, 2017). Although pain is one of several common symptoms in pediatric oncology, both pain and symptom assessment/management were included in the preliminary core set by expert panel members; highlighting pain as a priority symptom for pediatric oncology nursing assessment/management internationally.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pain assessment has been identified as an important quality measure for the outpatient care of children with cancer. 17 It is essential that we not only assess pain in this unique population, but also provide sufficient anticipatory guidance for caregivers along with at-home prescription medications.…”
Section: Discussionmentioning
confidence: 99%